Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1139/e90-027
|View full text |Cite
|
Sign up to set email alerts
|

Neoglacial history of the Coast Mountains near Bella Coola, British Columbia

Abstract: The maximum Holocene extent of glaciers in the study area is marked by late Neoglacial (Little Ice Age) terminal moraines. Moraine stratigraphy and 14C dates from a small number of sites suggest that glacier advance, almost as extensive as that of the late Neoglacial, occurred about 2500 14C years BP, and that late Neoglacial advance began well before 770 14C years BP (or the thirteenth century A.D.); glacier termini then stood close to the position of the climax moraines for several centuries. Dates of stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 15 publications
7
45
0
Order By: Relevance
“…This history is based on lichenometic and dendroglaciological investigations undertaken during the summer of 1997. Previous work in this region showed that most LIA terminal moraines date from the period between 1860 and 1900 (Desloges, 1987;Desloges and Ryder, 1990). Our data supplements these observations, adding to our knowledge of the LIA in coastal British Columbia.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…This history is based on lichenometic and dendroglaciological investigations undertaken during the summer of 1997. Previous work in this region showed that most LIA terminal moraines date from the period between 1860 and 1900 (Desloges, 1987;Desloges and Ryder, 1990). Our data supplements these observations, adding to our knowledge of the LIA in coastal British Columbia.…”
Section: Introductionsupporting
confidence: 82%
“…5). This curve provided an opportunity to reconsider the findings of Desloges (1987) and Desloges and Ryder (1990).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations